Potential and utilization of Indigofera sp shoot leaf meal as soybean meal substitution in laying hen diets - Rizki Palupi; Luki Abdullah; Dewi Apri Astuti; Sumiati . . (Jurnal Ilmu Ternak dan Veteriner, 2014)
The objective of this study was to determine the potential of Indigofera sp shoot leaf meal to substitute soybean meal in poultry diet. One hundred and sixty laying hens of Isa Brown strain, at 30 weeks old were used in this study and kept in individual cages. A Randomized Completely Design was applied with four treatments and four replications. The treatments were four levels of soybean meal protein substitution by Indigofera sp shoot meal protein in the diets: The level were 0% (R0), 15% (R1), 30% (R2) and 45% (R3). Eggs were collected daily and were evaluated on: weight, shell, albumen, yolk, intensity of yolk and haugh unit. Results showed that the nutrients content of Indigofera sp shoot leaf meal were crude protein 28.98%, crude fat 3.30%, crude fiber 8.49%, calcium 0.52% and phosphorus content was 0.34%. Indigofera sp shoot leaf meal contained a complete amino acids. The vitamin A and ß-carotene were high, i.e 3828.79 IU/100g and 507.6 mg/kg, respectively. It is concluded that Indigofera sp shoot leaf meal is potential to be used as an alternative source of protein. Substitute 45% soybean meal protein with Indigofera sp shoot leaf meal in laying hen diets increase egg quality and increase intensity of yolk colour to 55.88%.